Econometric Evidence on Statistical Anxiety of Engineering Students during the New Normal Setup - Casinillo, Emily L.; Lina, Jr., Eusebio R.; Casinillo, Leomarich F.; Batidor, Paulo G.; Lebante, Meralyn R. (Philippine Social Science Journal, 2022)
Students’ anxiety is one of the hindrances to good academic achievement due to its adverse impact on cognitive attitudes. This study aimed to ascertain the impact of socio-economic profile and learning experiences that are affected by the COVID-19 pandemic concerning students’ anxiety in learning statistics. The study used descriptive measures and econometric models to elucidate the anxiety level and its predictors of engineering students in a state university. Result reveals that the mean students’ perception score for their anxiety level is 34.19 (SD=4.94) and is classified as "anxious". This implies that students are experiencing uncomfortable moments and distressing learning behavior due to the adverse impact of the pandemic on the educational system. The econometric model reveals that older and female students are more anxious about learning statistics online. Findings showed that the level of difficulty and less creativity in statistics lessons contributes to the anxiety level of students. In conclusion, instructors/professors must motivate their students and build their interest in learning statistics by giving them realistic and enjoyable activities that suit online education. Furthermore, instructors/professors must undergo training that develops and improves their teaching strategies in statistics to become competitive educators in online learning amid the pandemic.